Leaf stoichiometric characteristics and responses of sea-buckthorn (Hippophae L.) involved in its niche-driven species distribution patterns across China - Zhang, Hongmei; Li, Xiaowei; Yang, Junlong; Yu, Shuang; Yang, Jun; Wang, Wenqiang (Frontiers in Plant Science, 2025)
IntroductionThe stoichiometric characteristics of leaves can indicate the nutrient limitations and ecological strategies of closely related plants. Sea-buckthorn is a unique species in China with economic and ecological value, yet nutrient limitations and environmental adaptation strategies in its main distribution areas remain unclear.MethodsHere, This study aims to explore the adaptive mechanism in different geographical environments and its impact on species substitution distribution patterns by analyzing the leaf stoichiometric characteristics of three species of sea-buckthorn (Hippophae rhamnoides, Hippophae tibetana and Hippophae neurocarpa).ResultsOur results reveal that the overall nitrogen (N) and phosphorus (P) concentrations of Sea-buckthorn leaves of are respectively 32.19 ± 4.96mg·g-1, and 2.03 ± mg·g-1 with an N/P ratio of 16.68 ± 4.01. Leaf N concentration significantly increased, with increasing longitude, and latitude. Leaf P concentration significantly increased, with the change of longitude. Among the three sea-buckthorn species, the N concentration of Chinese sea-buckthorn and Coastal sea-buckthorn exhibited increase significantly with latitude, whereas the N concentration of Tibetan sea-buckthorn showed significant variation with longitude. Through standardised major axis (SMA) regression, an allometric relationship was observed between the N and P concentrations across sea-buckthorn species. Notably, the N and P concentrations of Tibetan sea-buckthorn exhibited significant allometric relationship. Potential evapotranspiration and altitude were identified as the primary factors influencing N concentration, while slope and humidity index were the main drivers affecting P concentration. Additionally, average annual radiation and precipitation were found to influence the N/P ratio. The leaf stoichiometry of sea-buckthorn species revealed distinct adaptation mechanisms to their respective habitats, leading to niche-driven species distribution patterns along environmental gradients. Tibetan sea-buckthorn served as a transitional zone between the other two species.DiscussionTherefore, this study can provide basic data for the stoichiometric characteristics of sea-buckthorn leaves and the distribution pattern of species substitution, with provides a new ecological perspective on the relationship between species distribution and plant stoichiometric characteristics.